The Oxford Handbook of Poverty and Child Development 2012
DOI: 10.1093/oxfordhb/9780199769100.013.0025
|View full text |Cite
|
Sign up to set email alerts
|

Children Living in Rural Poverty: The Role of Chaos in Early Development

Abstract: Children who live in poor rural communities have a somewhat different context for development from urban children. Rural in comparison to urban communities have higher poverty rates; greater isolation from key services, such as schools and health care; and parents have more service related jobs with nonstandard work schedules. These factors are associated with poverty but also can add additional stress on rural family life that can contribute to more chaotic living conditions for young children, including diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 77 publications
2
32
1
2
Order By: Relevance
“…To be more specific, there seemed to be hardly any delay in receptive vocabulary from K-2 onwards, since the average score for the total group in our sample in K-2 and Grade 1 was at the national average level. These findings contradict previous findings in the same area (Driessen, 2013;Van der Vegt & Van Velzen, 2002;Vogels & Bronneman-Helmers, 2003), along with findings in other rural areas (Durham & Smith, 2006;Vernon-Feagans et al, 2012) that reported language delays in children from rural areas. Three observations, however, need to be made.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…To be more specific, there seemed to be hardly any delay in receptive vocabulary from K-2 onwards, since the average score for the total group in our sample in K-2 and Grade 1 was at the national average level. These findings contradict previous findings in the same area (Driessen, 2013;Van der Vegt & Van Velzen, 2002;Vogels & Bronneman-Helmers, 2003), along with findings in other rural areas (Durham & Smith, 2006;Vernon-Feagans et al, 2012) that reported language delays in children from rural areas. Three observations, however, need to be made.…”
Section: Discussioncontrasting
confidence: 78%
“…The low language proficiency of young children in rural areas is often overshadowed by discussions of problems in urban areas (Atav & Spencer, 2002;De Marco & Vernon-Feagans, 2013;Sheridan, Koziol, Clarke, Rispoli, & Coutts, 2014). Although children in rural and urban areas both lag behind in language proficiency, their early home experiences, prior to their school career, are starkly different as a consequence of differences in the socio-economic and cultural environment (Kloprogge, 2003;Miller & Votruba-Drzal, 2013;VernonFeagans & Cox, 2013): Rural areas are sparsely populated, the work force is less educated and less differentiated, and employment opportunities, in particular for the more highly educated, are rare (Fish & Pinkerman, 2003;Hospers & Reverda, 2012;Melis, 2013;Thissen, Fortuijn, Strijker, & Haartsen, 2010;Vernon-Feagans, Garrett-Peters, De Marco, & Bratsch-Hines, 2012;Vernon-Feagans et al, 2008). Therefore, this study will focus on how these socio-economic and cultural factors in rural areas relate to children's home environment, which we expect to be associated with early language and literacy development at the beginning of formal education.…”
Section: Introductionmentioning
confidence: 99%
“…Household chaos is one of those possible proximal mechanisms in the home that might help to explain how poverty exerts its influence on parenting and child behavioral and academic outcomes. Although chaos is found in non-poverty homes it occurs more often and with greater severity in poor homes because it has been found that such poverty related factors such as non-standard work hours, single parenthood, and fewer home resources are related to chaotic households (Valiente, Lemery-Chalfant & Reiser, 2007; Vernon-Feagans, Garrett-Peters, De Marco & Bratsch-Hines, 2012a). …”
Section: Household Chaos and Poverty As Predictors Of Child Regulatormentioning
confidence: 99%
“…The disadvantaged economies of life in rural contexts include fewer jobs with standard work hours, longer distances to work, childcare, and schools, limited public transportation, and less access to a variety of health and human resources that can promote a stable and predictable family life (Vernon-Feagans, Garrett-Peters, De Marco, & Bratsch, 2012). These unique features of rural life underscore the importance of examining the potential deleterious effects of living in chaotic households on the development of rural children.…”
Section: Introductionmentioning
confidence: 99%